Tshz1 Regulates Pancreatic β-Cell Maturation - Raum, Jeffrey C. (Diabetes, 2015)
The homeodomain transcription factor Pdx1 controls pancreas organogenesis, specification of endocrine pancreas progenitors, and the postnatal growth and function of pancreatic β-cells. Pdx1 expression in human-derived stem cells is used as a marker for induced pancreatic precursor cells. Unfortunately, the differentiation efficiency of human pancreatic progenitors into functional β-cells is poor. In order to gain insight into the genes that Pdx1 regulates during differentiation, we performed Pdx1 chromatin immunoprecipitation followed by high-throughput sequencing of embryonic day (e) 13.5 and 15.5 mouse pancreata. From this, we identified the transcription factor Teashirt zinc finger 1 (Tshz1) as a direct Pdx1 target. Tshz1 is expressed in developing and adult insulin- and glucagon-positive cells. Endocrine cells are properly specified in Tshz1-null embryos, but critical regulators of β-cell (Pdx1 and Nkx6.1) and α-cell (MafB and Arx) formation and function are downregulated. Adult Tshz1(+/−) mice display glucose intolerance due to defects in glucose-stimulated insulin secretion associated with reduced Pdx1 and Clec16a expression in Tshz1(+/−) islets. Lastly, we demonstrate that TSHZ1 levels are reduced in human islets of donors with type 2 diabetes. Thus, we position Tshz1 in the transcriptional network of maturing β-cells and suggest that its dysregulation could contribute to the islet phenotype of human type 2 diabetes.